OVOMUCOID (THE MOST IMPORTANT EGG WHITE ALLERGEN) AS A CAUSE OF SEVERE EGG ALLERGY:A REVIEW - Ahmed, Taha; Ayaz , Hafsa; Nisar, Dua; Moin , Areeba (Sanamed, 2024)
Hypersensitivity, or an allergy to highly valuable chicken egg proteins, is a prevalent symptomatic condition. It occurs when the immune system of a hypersensitive or allergic individual overreacts upon contact with egg allergens (egg proteins), triggering a complex immune response. Among these allergens, ovomucoid is the most allergenic, making up 11% of egg white. Ovomucoid is both thermostable and resistant to digestion, distinguishing it from other egg white proteins. While ovalbumin is the most abundant protein in egg white, ovomucoid is responsible for the majority of its allergic properties. Humans generally lack tolerance to both raw and cooked eggs due to the presence of this allergenic protein.Given the significance of ovomucoid in egg allergy, it has a direct impact on the quality of life of affected individuals. A better understanding of the role of various drug classes is essential for managing and treating egg allergy. Additionally, insights into embryogenesis may be critical in understanding the efficacy of these treatments in alleviating egg allergies. This knowledge could not only benefit individuals with egg allergies but also the egg production industry and society as a whole. Maintaining good health is one of the most crucial factors in serving our community, and addressing egg allergy is an important part of that.
Keywords: Egg allergy; ovomucoid; IgE-mediated food allergies; epidemic; embryogenesis; management; florfenicol; immunotherapies